DEVELOPMENT OF A WEBSITE-BASED ONLINE LEARNING MODE AS A MEANS OF INCREASING STUDENT INDEPENDENCE IN LEARNING - Trisnawati, Trisnawati; Dewantoro, Dewantoro; Mazdiyana, Mazdiyana (STMIK Pringsewu, 2022)
Now with advances in technology students and teachers alike can learn in the hands of technology. Currently, all countries in the world are facing the Covid-19 pandemic. All activities are restricted to prevent the spread of the Corona virus, including educational activities. In Indonesia, it has been more or less three months, all educational activities, from primary and secondary to tertiary levels, are conducted online. In this research concept, what researchers will do is how to make a website as a learning medium easily and can be understood by students and readers from all walks of life. Features can also be used properly so that students are interested and enthusiastic in independent learning. At the stage of making the website the researcher uses wordpress as a medium for editing the appearance of the theme or other features. So that it really can help researchers in simplifying and accelerating the creation of a website as a learning medium that helps students to learn independently online. At this stage the research model used is the waterfall model. Starting from the level and progress of the system, using this model has a systematic sequential software development method. In developing a website-based online learning mode as a means of increasing student independence in learning, teachers can update subject data, input new subject data, and delete unnecessary data. Subject data whose access time limit has been determined will be deleted by itself at a predetermined time. The teacher only needs to register as a teacher and can immediately become a teacher on the Website-Based Online Learning Mode Development Website as a Means to Increase Student Independence in Learning after passing certain predetermined phases and conditions. After completing teaching and learning activities, users can close the account or Logout from an existing account on the Website. After that, the website can be closed by closing the browser application which is used to open a website-based online learning mode development website as a means of increasing student independence in learning.